THE REASONS FOR PRACTICING SPORTS AT SCHOOL (Fiep Bulletin - online, 2015)
The reasons that determine sports practice, in the interior of school by teenagers are diverse, in view of that, the current study had as an objective to understand what were the actual reasons which led teenagers to practice sports activities within the school universe. We have attempted to investigate, from the delimitation of an investigation field and specific subjects, what are the reasons for sports practice within an educational reality. The methodology was designed according to the qualitative investigations paradigm, having as a reference the case study. The analysis and interpretation of information were made from Theme Units, which allowed for an understanding of what are the reasons that lead teenagers to practice sports in the school investigated. First, we observed three reasons that lead these teenagers to sports practice. We found as the first reason the personal reference, through which each teenager justifies his or her participation in some sports modality, by the simple fact that they like to practice it. Another reason which we have evidenced was the family influence, being as important for motivation, as for the choice of the sport to be practiced. Yet we point out, as the third reason that determines sports practice, the social reference, based on the teenagers' friendship ties in the school context investigated.
Keywords: Sport; School; Practice